Volume 11: Petroleum Technology 2020
DOI: 10.1115/omae2020-18222
|View full text |Cite
|
Sign up to set email alerts
|

Characterization of Rock and Fluid Properties for Low-Salinity Water Flooding of Highly Paraffinic Oil in a Deep Low-Permeability High-Pressure High-Temperature Offshore Carbonate Reservoir

Abstract: Characterization of the rock and fluids is an essential step in screening a reservoir for Low-Salinity Water Flooding (LSWF). A detailed characterization of rock and fluid properties using appropriate methods is being presented for LSWF in a low-permeability deep carbonate reservoir together with a critical analysis of findings. The techniques used are assessed against other possible alternative methods, with inferences drawn on advantages and disadvantages of each to better interpret and apply data so gathere… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
3
2

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(2 citation statements)
references
References 0 publications
0
2
0
Order By: Relevance
“…The acid number of the oil is~0.6 mg KOH as reported by Kakati et al [18]. For same set of rock and oil samples, Singh et al [19] had conducted a contact angle measurement using sessile drop method which showed a very weak water-wet state with seawater (contact angle of~102 • ). This also correlates with the high acid number of oil.…”
Section: Grid Model and Petrophysical Propertiesmentioning
confidence: 83%
See 1 more Smart Citation
“…The acid number of the oil is~0.6 mg KOH as reported by Kakati et al [18]. For same set of rock and oil samples, Singh et al [19] had conducted a contact angle measurement using sessile drop method which showed a very weak water-wet state with seawater (contact angle of~102 • ). This also correlates with the high acid number of oil.…”
Section: Grid Model and Petrophysical Propertiesmentioning
confidence: 83%
“…The acid number of the oil is ~0.6 mg KOH as reported by Kakati et al [18]. For same set of rock and oil samples, Singh et al [19] had conducted a contact angle measurement using sessile drop method which The component analysis of oil samples was analyzed from ASTM D2887 simulated distillation. The C7+ hydrocarbon component proportions obtained from the analyses were combined into one component as given in Table 5.…”
Section: Grid Model and Petrophysical Propertiesmentioning
confidence: 99%